Wild Animals Maintained in Jamunkhadi Mini Zoo, Conservation Status, and their Occurrence in Jhapa District, Nepal - Rai, Tapil Prakash (Adhyayan Journal, 2022)
The Jamunkhadi Mini Zoo has been in operation for 15 years and has maintained various species of wild animals, although the majority of them are either unidentified or misidentified on their species labels. Publications revealing the occurrence of wild animals in the Jhapa District are scanty. This study identifies wild animals maintained at the Jamunkhadi Mini Zoo and surveys its place of collection. A wild animal survey form was filled with the officials of the Jamunbari Community Forest and its zookeepers. High-resolution photographs of all the wild animals in the mini zoo were taken and identified with the help of relevant species identification guide books and experts in the various wildlife disciplines. A field survey was carried out by a team of 3-5 researchers to confirm the occurrence of indigenous wild animals in the forests of Jhapa. A total of 28 species of wild animals comprised of six reptile species, seven bird species, and 15 mammal species are identified and listed at the Jamunkhadi Mini Zoo. Of the 28 species maintained at the zoo, 9 (32.14%) are listed as globally threatened; whereas 15 species (53.57%) are listed as nationally threatened, and of those 28 species, 26 are confirmed to occur in the Jhapa. The Leopard Cat, Prionailurus bengalensis has probable habitat in the northern forests that connect with Ilam District in the south. The Sloth Bear, Melursus ursinus has not been recorded in Jhapa.